Prevalence of arsenic contamination in rice and the potential health risks to the Bahamian population—A preliminary study - Watson, Carlton; Gustave, Williamson (Frontiers in Environmental Science, 2022)
Rice is among the most important staple foods worldwide. However, the consumption of rice and rice-based food products poses a potential health risk since rice is a paddy crop that is well known to accumulate high concentrations of arsenic (As) in its grain. In The Bahamas, although rice is heavily consumed, it is not grown locally. Instead, all the consumed rice and its derived products are imported. Recent food surveys in the major rice exporting countries have shown that a significant portion of their market rice products is contaminated with As. However, to date, the prevalence of As in the rice foods available in The Bahamas remains unknown. Therefore, in this study, we surveyed the occurrence of As in a selection of rice and rice products that were on sale in the Bahamian market. A total of 21 different rice brands were collected. The concentration of As and the potential health risk were estimated by target hazard quotient (THQ), hazard index (HI), and lifetime cancer risk (LCR). Our results showed that only the blue ribbon samples had an estimated inorganic arsenic (iAs) concentration above the World Health Organization (WHO) safety limits (200 μg/kg), which is based on global average consumption. However, when we factor for average rice consumption in The Bahamas, 79% of the rice samples had iAs concentration values indicative of carcinogenic risks and 57% had iAs concentration values that suggested non-carcinogenic health risks. Based on our results, we recommend urgent follow-up studies to further test rice varieties that show the greatest LCR and HI values and to also broaden the study to include more off-brand/generic varieties, cooked rice, and drinking water.